Cell-Type Dependent Regulation of the Electrogenic Na+/HCO3− Cotransporter 1 (NBCe1) by Hypoxia and Acidosis in Glioblastoma - Giannaki, Marina; Ruf, Debora E.; Pfeifer, Emilie; Everaerts, Katharina; Heiland, Dieter Henrik; Schnell, Oliver; Rose, Christine R.; Roussa, Eleni (International Journal of Molecular Sciences, 2022)
Glioblastoma multiforme (GBM) is the most common and malignant brain tumour. It is characterised by transcriptionally distinct cell populations. In tumour cells, physiological pH gradients between the intracellular and extracellular compartments are reversed, compared to non-cancer cells. Intracellular pH in tumour cells is alkaline, whereas extracellular pH is acidic. Consequently, the function and/or expression of pH regulating transporters might be altered. Here, we investigated protein expression and regulation of the electrogenic sodium/bicarbonate cotransporter 1 (NBCe1) in mesenchymal (MES)-like hypoxia-dependent and -independent cells, as well as in astrocyte-like glioblastoma cells following chemical hypoxia, acidosis and elucidated putative underlying molecular pathways. Immunoblotting, immunocytochemistry, and intracellular pH recording with the H+-sensitive dye 2′,7′-bis-(carboxyethyl)-5-(and-6)-carboxyfluorescein were applied. The results show NBCe1 protein abundance and active NBCe1 transport. Hypoxia upregulated NBCe1 protein and activity in MES-like hypoxia-dependent GBM cells. This effect was positively correlated with HIF-1α protein levels, was mediated by TGF-β signalling, and was prevented by extracellular acidosis. In MES-like hypoxia-independent GBM cells, acidosis (but not hypoxia) regulated NBCe1 activity in an HIF-1α-independent manner. These results demonstrate a cell-specific adaptation of NBCe1 expression and activity to the microenvironment challenge of hypoxia and acidosis that depends on their transcriptional signature in GBM.
CRIS-Team Scopus Importer:2023-09-13
Keywords: cancer; growth factors; pH regulation